Language abilities in bilingual children: The effect of family background and language exposure on the development of Turkish and Dutch. (October 2020) - Altinkamis, Feyza; Simon, Ellen
Aims and objectives: The study investigates the effects of family background and language exposure on the language abilities of Turkish-Dutch bilingual children in their heritage language, Turkish, as well as in the majority language, Dutch. Methodology: Thirty-five children (3;01-6;11) participated in the study. All children took two standardized proficiency tests: CELF-Preschool 2 in Dutch and TEDİL in Turkish. Parents were interviewed on the family background and on the children's use of and exposure to Dutch and Turkish. Data and analysis: Children's test scores in Dutch and Turkish were analyzed in relation to the amount of exposure to Dutch and Turkish and the socio-economic and linguistic background of the parents. Findings: The results reveal that the children's home context—both the linguistic background of the parents and the socio-educational level of the mother—affected the children's scores, especially for Dutch. The amount of exposure to and use of Dutch and Turkish was correlated to the Dutch and Turkish scores. A qualitative discussion of children's profiles revealed that children's performance can only be fully understood when details of the home context, obtained through interviews with the parents, are taken into account. Originality: To date, few studies on bilingual children from families with a migration background have examined young children's general language abilities in both the heritage language and the majority language. Implications: The study raises awareness of the importance of evaluating bilingual children's language proficiencies in both languages, considering the effects of family background and language exposure on children's bilingual language development. Limitations: The children's language abilities were mapped on the basis of widely recognized standardized tests originally developed for the assessment of monolingual children. As more bilingual instruments are being tested and developed, future research will benefit from these tools.